1980
DOI: 10.1007/bf02024198
|View full text |Cite
|
Sign up to set email alerts
|

Are the anti-allergic actions of theophylline due to antagonism at the adenosine receptor

Abstract: Adenosine potentiated anaphylactic histamine release from isolated rat mast cells in a dose-dependent manner between 10(-8) and 10(-5) M. Adenosine was found to be present during a normal incubation of mast cells, but the concentration was low (2 x 10(-8) M). In rat plasma the concentration was 1.5 x 10(-7) M. The effect of 10(-5) M adenosine was dose-dependently inhibited by theophylline. 50% inhibition was found at 3 x 10(-5) M theophylline. Cyclic nucleotide phosphodiesterase inhibition required much higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The antiallergic actions of theophylline has been suggest ed to be due to an inhibition of the effects of adeno sine on the mast cell, rather than direct effects on cyc lic AMP metabolism [7]. In our experiments, not only theophylline but also traxanox sodium or DSCG were confirmed to antagonize the effect of adenosine in vitro.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The antiallergic actions of theophylline has been suggest ed to be due to an inhibition of the effects of adeno sine on the mast cell, rather than direct effects on cyc lic AMP metabolism [7]. In our experiments, not only theophylline but also traxanox sodium or DSCG were confirmed to antagonize the effect of adenosine in vitro.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, adenosine which potentiates the ana phylactic or A23187-induced histamine release from the mast cells is suggested to be an important modula tor of mast cell function in complex tissues [7,21]. The antiallergic actions of theophylline has been suggest ed to be due to an inhibition of the effects of adeno sine on the mast cell, rather than direct effects on cyc lic AMP metabolism [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, these observations may have been affected by the following: (i) theophylline acts as an adenosine antago nist [9,10], non-competitive inhibition with respect to pyridoxal could therefore be the result of theophylline competing with adeno sine triphosphate (ATP) for enzyme binding [11], studies with low ATP concentrations in hemolysates could not be done to investigate this possibility due to the ubiquitous use of ATP in various biochemical reactions, and (ii) both pyridoxal and PLP are bound by hemoglobin [8,12], which may also affect the kinetics of the pyridoxal kinase-cata lyzed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is quite likely that the enterochromaffinlike cells, recently isolated from the canine gastric muco sa, are the source of the secretagogue-stimulated hista mine release [3], the canine gastric mucosa is very rich in mast cells, and it has not been determined with certainty that the mast cell histamine content has no effect on gas tric mucosal histamine release [19], Adenosine via A| receptors has been shown to enhance stimulated hista mine release from canine gastric mast cells as well as from human and rodent pulmonary mast cells [2,[20][21][22], The effect of adenosine can be inhibited with the adenosine receptor antagonist theophylline, and the possibility that theophylline ameliorates asthma by inhibiting mediator release has been proposed by several investigators [23], Our data demonstrated that adenosine infused to gas tric arterial concentrations of 30 and 100 \xM had no sig nificant effect on pentagastrin-stimulated gastric hista mine release. Although the between-dog variability in response to pentagastrin was large, overall the effect of the two concentrations of adenosine was not statistically dif ferent from the vehicle.…”
Section: Discussionmentioning
confidence: 99%